2003
DOI: 10.1074/jbc.m300544200
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Mechanism for Receptor-activated Canonical Transient Receptor Potential 3 (TRPC3) Channels

Abstract: Canonical transient receptor potential 3 (TRPC3) is a receptor-activated, calcium permeant, non-selective cation channel. TRPC3 has been shown to interact physically with the N-terminal domain of the inositol 1,4,5-trisphosphate receptor, consistent with a "conformational coupling" mechanism for its activation. Here we show that low concentrations of agonists that fail to produce levels of inositol 1,4,5-trisphosphate sufficient to induce Ca 2؉ release from intracellular stores substantially activate TRPC3. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
153
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(169 citation statements)
references
References 38 publications
(60 reference statements)
16
153
0
Order By: Relevance
“…This they interpreted as being indicative of a coupling, lipase-independent role of PLC␥ in agonist-dependent cation entry regulation. However, our experiments showing the inability of BCR stimulation to activate TRPC3 when expressed in the PLC␥2-deficient DT40 cell line indicate a requirement for PLC-dependent DAG generation for channel activity (8,14,40). This is supported by the finding that stimulation of the Gq/PLC␤-coupled muscarinic receptor pathway or challenging the cells with OAG, efficiently activated TRPC3-mediated cation entry in PLC␥-KO DT40 cells, i.e.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This they interpreted as being indicative of a coupling, lipase-independent role of PLC␥ in agonist-dependent cation entry regulation. However, our experiments showing the inability of BCR stimulation to activate TRPC3 when expressed in the PLC␥2-deficient DT40 cell line indicate a requirement for PLC-dependent DAG generation for channel activity (8,14,40). This is supported by the finding that stimulation of the Gq/PLC␤-coupled muscarinic receptor pathway or challenging the cells with OAG, efficiently activated TRPC3-mediated cation entry in PLC␥-KO DT40 cells, i.e.…”
Section: Discussionsupporting
confidence: 74%
“…Despite the existence of multiple potential phosphorylation sites in the TRPC3 primary sequence, there are very few studies specifically addressing the role of kinases in TRPC3 activity. Recent studies provided evidence that PKC (14,41) and protein kinase G negatively regulate TRPC3 (42). By using HEK293 cells stably expressing TRPC3 we found that the non-receptor tyrosine kinase Src is absolutely required for signaling to TRPC3, whether through receptor activation, or through application of OAG.…”
Section: Discussionmentioning
confidence: 99%
“…When exogenously expressed some TRPC channels displayed SOCE activity [12][13][14]. However, numerous studies also demonstrated that TRPC channels did not operate as SOCE channels, but rather are gated by second messengers like Ca 2+ or diacylglycerol (DAG; [15][16][17]). Hence, the involvement of TRPC channels in the SOCE mechanism is a controversial issue, and appears to dependent on the cell types investigated, and importantly on the expression level of the TRPC [14,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…That at least one of the PM proteins interacting with IP 3 Rs is TRPC3 is shown in Fig. 4C, which shows that IP of TRPC3 co-immunoprecipitated IP 3 R3, the co-IP was reduced by cell stimulation, and the IP 3 Rs-TRPC3 complex was reformed by inhibition of carbachol-stimulated cells with atropine.Although several studies (17,19,28,45,46), including ours (18, 30), suggested that TRPC3 can function as SOCs, others concluded that this is not the case (15,47,48). However, the behavior of TRPC3 in native cells was examined before only in one study using pontine neurons from P3-P8 rats.…”
mentioning
confidence: 98%